Pengembangan Media Pembelajaran Alkitab Berbasis Papan Permainan Bagi Anak Sekolah Minggu - Hariyanto, Elshadai Charis (Shift Key : Jurnal Teologi dan Pelayanan, 2025)
This study aims to develop a Bible learning medium for Sunday school children through an educational and interactive board game approach at Beth-El Tabernacle Church Kristus Alfa Omega, Patean, Kendal. The rapid advancement of technology has influenced children’s learning styles, creating a demand for innovation in religious teaching methods, particularly within the Sunday school context. This research employs a Research and Development (R&D) design using the Lima Tahap (MANTAP) model, which includes identification of research problems, review of relevant theories, and feasibility testing conducted both qualitatively by 10 experts and quantitatively by 30 experts. The study produced a board game titled “Bible’s Back In Time Challenge” (BBC). The results indicated that the game achieved a validation score range of 90%–100% across sixteen statement items, signifying that the board game is deemed suitable and acceptable as a Bible learning medium for Sunday school children.